The Effectiveness of Using a Bilingualized Dictionary for Determining Noun Countability and Article Selection - Chan, Alice Yin Wa (Lexikos, 2017)
This article discusses the use of a bilingualized dictionary, namely Oxford Advanced Learner’s English–Chinese Dictionary 8 (OALECD8), by advanced Hong Kong Cantonese ESL learners in the determination of noun countability and associated article use. A homogenous group of 30 English majors in a local university participated in the study, which consisted of a noun countability and article selection task without and with the use of the dictionary. The results show that although bilingualized dictionaries are useful in helping learners determine noun countability and associated article use, learners often misinterpret dictionary information and model on inappropriate structures, resulting in article errors and/or wrong countability judgments. Chinese translations are also sometimes sources of errors. The results of the study provide lexicographers with signposts to the selection of noun information to be included in a learner’s dictionary. More explicit information about noun countability and related article use should be provided in a more user-friendly arrangement. ESL teachers are also advised to engage advanced learners in analyses uncovering the different syntactic requirements of equivalent vocabulary items in the target and source languages when using a bilingualized dictionary.